2012
DOI: 10.1007/978-1-4614-1704-0_18
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Semantic and Episodic Forms of Self-Knowledge: Insights from Functional Neuroimaging

Abstract: Abstract:Throughout evolution, hominids have developed greater capacity to think about themselves in abstract and symbolic ways. This process has reached its apex in humans with the construction of a concept of self as a distinct entity with a personal history. This chapter provides a review of recent functional neuroimaging studies that have investigated the neural correlates of such "higher-level" aspects of the human self, focusing in particular on processes that allow individuals to consciously represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 91 publications
(126 reference statements)
2
21
0
Order By: Relevance
“…Autobiographical facts are typically relatively idiosyncratic (e.g., I know that my brother owns an old blue station wagon), which is compatible with the presumed role of the temporal pole in the retrieval of information associated with unique objects and individuals (e.g., [24,25]). The greater medial prefrontal activation for PS than for GS in Maguire's neuroimaging studies is consistent with the putative role of this brain region in self-referential processing [26]. Interestingly, compared to EM, PS has been associated with lesser activity in these three brain regions (i.e., medial prefrontal cortex, temporal pole, and retrosplenial cortex), as well as in the hippocampus [21,22,27].…”
Section: When Ps Appears Similar To Semantic Memory (And Dissimilar Tsupporting
confidence: 70%
See 1 more Smart Citation
“…Autobiographical facts are typically relatively idiosyncratic (e.g., I know that my brother owns an old blue station wagon), which is compatible with the presumed role of the temporal pole in the retrieval of information associated with unique objects and individuals (e.g., [24,25]). The greater medial prefrontal activation for PS than for GS in Maguire's neuroimaging studies is consistent with the putative role of this brain region in self-referential processing [26]. Interestingly, compared to EM, PS has been associated with lesser activity in these three brain regions (i.e., medial prefrontal cortex, temporal pole, and retrosplenial cortex), as well as in the hippocampus [21,22,27].…”
Section: When Ps Appears Similar To Semantic Memory (And Dissimilar Tsupporting
confidence: 70%
“…In functional neuroimaging studies, medial prefrontal, temporal polar, retrosplenial, and precuneus regions seem to be critical for the representation of personal aspects of semantic memory ( Figure I). The medial prefrontal cortex, heavily involved in self-referential processing [26], is active in the most abstract forms of PS, namely autobiographical facts and self-knowledge (with activity centered around BA 10 in both cases). The temporal poles, known to support the representation of unique entities (e.g., [24,25]), are one of the brain regions most robustly associated with the representation of autobiographical facts.…”
Section: Box 2 Ps As a Sub-domain Of Semantic Memorymentioning
confidence: 99%
“…Evidence shows that RSP/PCC encodes contextual information to disambiguate stimuli (Miller, Vedder, Law, & Smith, 2014) and is critically implicated in self-referential processes linked to introspection and recollection (Kim, 2012;Schmitz & Johnson, 2007;Whitfield-Gabrieli et al, 2011), representation of self-knowledge in time (D'Argembeau & Salmon, 2012), and internal subjective decision-making (Johnson et al, 2005). Studies on meta-memory have suggested that confidence assessment during recollection is associated with differential engagement of self-monitoring functions mediated by the default network (Chua, Schacter, & Sperling, 2009), within which the RSC/PCC and precuneus both are key nodes.…”
Section: Discussionmentioning
confidence: 98%
“…Quite remarkably, however, there is growing evidence that the processing of various types of self-related contents – which form parts of the self-as-object – is commonly associated with activation of the medial portion of the prefrontal cortex (for recent reviews and meta-analyses, see Northoff et al, 2006; van der Meer et al, 2010; Qin and Northoff, 2011; Denny et al, 2012; D’Argembeau and Salmon, 2012; Murray et al, 2012; Wagner et al, 2012; Martinelli et al, 2013). …”
Section: Medial Prefrontal Involvement In Processing Self-related Conmentioning
confidence: 99%
“…This idea that we attach unique significance to self-related contents may prove useful for interpreting one of the most consistent findings that has emerged from neuroimaging research on self-processing. Over the past decade, a growing number of studies have shown that the ventromedial prefrontal cortex (vMPFC) is activated when people contemplate various aspects of themselves and their life, such their traits, experiences, preferences, abilities, and goals (Northoff et al, 2006; Lieberman, 2010; D’Argembeau and Salmon, 2012; Wagner et al, 2012; Martinelli et al, 2013). However, while it is now common to see the vMPFC referenced as a “self region,” the precise mental operations mediated by this area remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%